บทบาทของอุตสาหกรรมสิ่งทอกับการพัฒนาระเบียงเศรษฐกิจภาคตะวันออก (EEC) - โอทองคำ, มณเธียร (Journal of Applied Economics and Management Strategy, 2018)
The Eastern Economic Corridor (EEC) is a strategic plan under the Thailand 4.0 model, derived from the Eastern Seaboard (ESB) plan. Its aim is to foster investment for the industrial sector of Thailand, increasing the economy’s competitiveness, and enabling long-term growth. Chonburi, Rayong, and Cha-Cheng-Sao are the regions focused on with over 13,000 square kilometers. The region will be a hub for industry, malls, investment, and logistics. This will enhance Thailand’s position as the hub of the ASEAN economy. The Office of the National Economic and Social Development Board has proposed the aforementioned region under the management system of the EEC committee for the year 2017-2021. This research study aims 1) to examine the situation and trends of the textile industry in the development of the Thai economy today and in the future; and 2) to analyze the potential of the textile industry as part of the EEC integrated plan. Research shows that there is a downward trend in traditional textile production and exports. However, there is an increasing trend for technical and functional textiles, which incorporate advanced technology and innovation in their production. This is attractive for commercial investors, as expected returns are high, especially for Protective textiles. This progressive trend, coupled with the EEC plan, is seen as a great opportunity for the textile industry, especially the technical and functional textiles, whose qualities are compatible with the ten priority industries. It is important that technological and personnel support from the public sector be granted in order for the textile industry to be a solid driver of the economy. Keywords: Eastern Economic Corridor, Innovation, Strategy, Technical and Functional Textiles